An Analysis of Indirect Speech Acts Performed by Main Character in Joker Movie - Rahayu Ramadani Limbong; Sofyan A. Gani; Tengku Maya Silviyanti (Research in English and Education Journal, 2022)
Language is a tool to communicate to each other. To make beginner understand about English, they must use media to learn. movie is chosen to be analyzed the importance of educational values as a part of our life. This research discusses the using of Indirect Speech act in Joker Movie from the utterance of the main character. The purpose of this study is to determine the types and the functions of indirect speech acts used by the main character in the Joker Movie. The research was conducted using a qualitative descriptive method, in which the researcher gathered information from the script and dialogue from the movie, identified the types and functions of the characters indirect speech act based on Searle’s theory, and then draw the conclusions. To focus on the research, the researcher found eight data in his research. The result of this research is the researcher found two types which are declarative and interrogative of indirect speech act used in Joker Movie and there are six functions of the indirect speech act used in Joker Movie there are declare, commanding, condolence, refusal, blame, and promise. Finally, this study concludes that indirect speech act has types but different meaning. Context of situation and social status is really important of the using of indirect speech.